2020
DOI: 10.1101/2020.01.15.907501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Harnessing intrinsic fluorescence for typing of secondary structures of DNA

Abstract: ABSTRACTDNA is polymorphic since, despite its ubiquitous presence as a double-stranded helix, it is able to fold into a plethora of other secondary structures both in vitro and in cells. Despite the considerable advances that have been made in understanding this structural diversity, its high-throughput investigation still faces severe limitations. This mainly stems from the lack of suitable label-free methods, combining a fast and cheap experimental … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…It is well known that Qs produce a fluorescent emission band around 400 nm when excited with wavelength in the range 255–265 nm [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Our fluorescence experiments revealed that both TBA and 5′-DMAzo-TBA, annealed in 100 K buffer were unable to produce a significant emission band in the range 300–460 nm ( Figure 5 A, black and red lines respectively).…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that Qs produce a fluorescent emission band around 400 nm when excited with wavelength in the range 255–265 nm [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Our fluorescence experiments revealed that both TBA and 5′-DMAzo-TBA, annealed in 100 K buffer were unable to produce a significant emission band in the range 300–460 nm ( Figure 5 A, black and red lines respectively).…”
Section: Resultsmentioning
confidence: 99%
“…the increase of the quantum yield (QY) compared to a mixture of the non-interacting mononucleotides accompanied by longer lifetimes. 27,30,56,57 The highest fluorescence QY measured until now for a G4 is that of the 5′d[(G3T)3G3]-3′ sequence, folded in parallel arrangement, i.e. QY between 2 and 4x10 -3 , 56,58 one order of magnitude more than guanosine monomer (~1x10 -4 ).…”
Section: Main Deactivation Paths 31 Fluorescence and Non Radiative-pmentioning
confidence: 97%
“…3 Recently, their intrinsic fluorescence has started to be investigated for the development of biosensors. 4,5 In this respect, a better understanding of the factors that affect the G4 fluorescence is necessary.…”
Section: Introductionmentioning
confidence: 99%